European and Best Practice Bank Resolution Mechanisms : An Assessment and Recommendations for Policy and Legal Reforms - World Bank (Washington, DC, 2013)
The process of bank resolution, or the procedure for handling insolvency of banks using a range of tools, including alternatives to standard bankruptcy processes, has gained major traction since the experience of the 2008-09 financial crisis. In this context, this report reviews models for bank resolution that provide increased flexibility and describes several of the supervisory, legal and instrumental tools that can be used under modernized bank resolution procedures. As well, it looks at the recent European Commission proposals on this matter which take into account international best practices experiences. It also highlights areas of reform and areas where further regulatory considerations and priorities should be considered. The report reviews the bank resolution regimes of a group of European countries as well as those of two non-EU countries to highlight advantages as well as gaps in the legal and regulatory frameworks. This report surveys the banking and deposit insurance laws of six European countries : Poland, the Czech Republic, Germany, Spain, the U.K., and Croatia. Remedial enforcement measures for distressed banks and for bank resolution reveals that adoption of the EU legislative proposals, as described in the EC Communication, would require significant changes in legislation in four of the six countries. The report also reviews the laws of Canada and the U.S. for comparison, as implementation of their laws has already utilized several of the resolution instruments and mechanisms being considered.